2019
DOI: 10.3168/jds.2018-15576
|View full text |Cite
|
Sign up to set email alerts
|

Milk and kefir maintain aspects of health during doxorubicin treatment in rats

Abstract: Doxorubicin (DOX), a powerful anthracycline antibiotic commonly used to treat a wide variety of cancers, is associated with the production of reactive oxygen species that cause oxidative damage, resulting in cardiac dysfunction. Components of dairy may have protective effects against DOX-induced cardiac damage. Kefir is a naturally fermented milk product containing antioxidants, probiotic bacteria, and yeast in addition to the protective components of dairy. We explored the effects of dietary milk and kefir on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Gut microbiota is closely linked to daily diets, and even a short-term adjustment in the diet, as short as 5 days, is sufficient to alter the composition of gut microbiota and induce corresponding changes for adaptation [138]. Stewart et al discovered that long-term ingestion of milk or kefir (a milk containing lactic acid bacteria) could be beneficial for rats treated with doxorubicin [139]. Additionally, it has been demonstrated that the administration of phenylalanine-butyramide (a novel synthetic derivative of butyric acid) can have a positive effect on DIC [18].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Gut microbiota is closely linked to daily diets, and even a short-term adjustment in the diet, as short as 5 days, is sufficient to alter the composition of gut microbiota and induce corresponding changes for adaptation [138]. Stewart et al discovered that long-term ingestion of milk or kefir (a milk containing lactic acid bacteria) could be beneficial for rats treated with doxorubicin [139]. Additionally, it has been demonstrated that the administration of phenylalanine-butyramide (a novel synthetic derivative of butyric acid) can have a positive effect on DIC [18].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…The weight of each rat was measured on a weekly basis using a weight scale following the method described by Stewart et al (2019).…”
Section: Feed and Water Intakes And Body Weightmentioning
confidence: 99%
“…Secara invitro dan in vivo, peningkatan berat badan diikuti dengan peningkatan kolesterol [72] Bakteri dan khamir sebagai komponen kefir menghasilkan bile salt hydrolase, enzim katalase ini mampu dekonjugasi asam empedu dan meningkatkan ekskresi kolesterol dalam fases, sehingga membantu penurunan TC [82]. Beberapa komponen bioaktif kefir menurunkan TC dan LDL manusia [74], kefir dapat mengikat lemak dan mengekresikan lemak melalui fases, juga mengakibatkan penurunan berat badan [83]. Kefir kaya asam amino [30], yang secara signifikan mengurangi ekspresi SREBP1c, PPARγ, and FAS, tetapi tidak mengurangi ACC adiposit 3T3-L1 matur.…”
Section: Pengaruh Pemberian Whey-ksk Terhadap Total Tc Pada Model Sel...unclassified